FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS MELUR KOTA PEKANBARU TAHUN 2014 - Handoko, Bobi (Ensiklopedia of Journal, 2020)
The low coverage of Exclusive breast feeding Clinics working relic in Melur in the city of Pekanbaru in 2012 i.e. 26,76%. While the targets set Renstra 70%. This research aims to know the factors that relate to Exclusive breast feeding and he knows what the level of mother's age, occupation, education, knowledge, the role of the family and IMD related factor is breast feeding on infants in the region Work Puskesmas Melur years 2014. Research methods design with Cross Sectional was held in May-June of 2014 in the city of Pekanbaru Melur Clinics Work. the number of samples of 82 and a population of 552. Measuring instrument used was a questionnaire. Data-processing by computerization. Data analysis for test with bivariat Chi-Square. The results showed that the variables have a meaningful relationship of exclusive breast feeding for the variable levels of employment p value 0,013 and IMD p value 0,017. Conclusion: there is a meaningful relationship between the employment rates of mothers, and IMD. Suggestions: Expected Clinics play an active role in providing guidance on early breastfeeding Exclusive breast feeding. Counseling emphasized to mothers have babies 6-12 months. Expected place instances of Working Moms may give allowances to mothers who have babies in order to provide Exclusive breast milk.